Influence of railway induced vibrations on structures and humans in urban areas - Naumovski Nikola, Hristovski Viktor, Krstevska Lidija (Croatian Society of Civil Engineers - HSGI, 2022)
Rail traffic is a significant source of vibration that can affect the quality of life of people living near busy railways. The paper proposes an integrated methodology for analysis of the impact of vibrations from railway traffic on people and buildings and measures for reduction of their effect. The research has grasped in-situ measurements and numerical modelling of railway traffic-induced vibrations. The proposed integrated methodological approach is specifically implemented on the section of the active railway line Kumanovo-Deljadrovce, N. Macedonia. The knowledge gained in this research is intended to represent a good basis for defining national standards for this increasingly relevant issue.
Keywords: railway vibrations, in-situ vibration measurement, finite element method, attenuation curve